Pengembangan Model Prediktif dan Framework Strategis Peningkatan Loyalitas Konsumen E-Commerce Berbasis Subjective Well-Being - Ade Perdana Siregar; Syahmardi Yacob; Idham Khalik; Raja Sharah Fatricia (Jurnal Manajemen dan Pemasaran Digital, 2025)
The growth of the digital economy in Indonesia has driven a significant rise in e-commerce platform usage, paralleling high internet penetration across various regions, including Jambi Province. However, the increase in the number of e-commerce users is not always matched by consumer loyalty, given the intense competition among platforms and the ease with which consumers can switch services. This study aims to analyze the impact of trust and experience quality on e-commerce loyalty, with subjective well-being serving as a mediating variable among e-commerce users. A quantitative methodological approach was employed, involving model development and testing via Structural Equation Modeling (SEM) using SmartPLS software to examine the relationships between variables and the mediation effects within the research model. The results indicate that trust has a positive and significant effect on both subjective well-being and e-commerce loyalty. Experience quality also exerts a positive and significant influence on subjective well-being and e-commerce loyalty. Furthermore, subjective well-being has a positive and significant impact on e-commerce loyalty. Mediation analysis reveals that subjective well-being significantly mediates the effects of trust and experience quality on e-commerce loyalty. These findings demonstrate that consumer loyalty is influenced not only by functional aspects but also by the psychological well-being experienced while using e-commerce platforms.